2019
DOI: 10.1016/j.chom.2019.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Dengue NS2A Protein Orchestrates Virus Assembly

Abstract: Highlights d Dengue NS2A recruits C-prM-E structural proteins and a protease to virion assembly site d A cytosolic loop of NS2A recruits the 3 0 UTR of viral RNA to virion assembly site d A coordinated C-prM cleavage enables viral RNA encapsidation and virion formation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 68 publications
2
82
0
Order By: Relevance
“…These mutants, which were incompetent for viral assembly, (Gly-11-Ala, Glu-20-Ala, Glu-100-Ala, Gln-187-Ala, and Lys-188-Ala), could be rescued in trans by expressing wild-type NS2A or a mutant unable to support vRNA replication [86]. Further studies demonstrated that despite similar levels of viral protein synthesis and ER membrane rearrangements between wild-type RNA and the Gly-11-Ala mutant, the latter failed to form viral particles, as assessed by transmission electron microscopy, and reduced release of extracellular vRNA [87]. Moreover, the Gly-11-Ala mutant showed a significant decrease in the C-prM cleavage which resulted in an altered cellular localization of C, a decreased expression of E and an abrogation of prM expression.…”
Section: Post-replicative Functions Of Ns Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…These mutants, which were incompetent for viral assembly, (Gly-11-Ala, Glu-20-Ala, Glu-100-Ala, Gln-187-Ala, and Lys-188-Ala), could be rescued in trans by expressing wild-type NS2A or a mutant unable to support vRNA replication [86]. Further studies demonstrated that despite similar levels of viral protein synthesis and ER membrane rearrangements between wild-type RNA and the Gly-11-Ala mutant, the latter failed to form viral particles, as assessed by transmission electron microscopy, and reduced release of extracellular vRNA [87]. Moreover, the Gly-11-Ala mutant showed a significant decrease in the C-prM cleavage which resulted in an altered cellular localization of C, a decreased expression of E and an abrogation of prM expression.…”
Section: Post-replicative Functions Of Ns Proteinsmentioning
confidence: 99%
“…More recently, a detailed mechanism of the function for NS2A during DENV virus assembly was described by Xie and collaborators [86,87]. The authors reported a set of mutations that specifically impaired virus assembly without affecting vRNA synthesis.…”
Section: Post-replicative Functions Of Ns Proteinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specific mutations in NS2A appear to hinder packaging [28,29]. It has recently been shown that dengue and ZIKV NS2A recruits the viral genome by binding specifically to the highly-structured 3 UTR and the C-prM-E complex and protease to site of virion assembly coordinating capsid loading and subsequent virion assembly [30,31]. The NS3 helicase separates nascent (+) strand from template (−) strand starting at the 3 end [32] and NS5 binds the 5 UTR of the (+) sense viral genome and translocates to the 3 end upon cyclization of the RNA to begin genome replication [33,34].…”
Section: Introductionmentioning
confidence: 99%